A STUDY OF SOME PHYSICAL CAPABILITIES OF THE LEGS AND THEIR RELATIONSHIP TO THE SKILL OF SCORING ACCURACY FROM FIXED KICKS IN FOOTBALL - Assistant Lecturer, Younis Sabih Abdullah (American Journals, 2023)
The research aims to identify the extent of the effect of the physical capabilities of the legs and its relationship to the skill of scoring from fixed kicks in football by looking at the performance of the players in performing the single skill, as it was found that those strikes were not used in scoring correctly, which led the researcher to study that weakness in scoring from stability, as it was found The researcher found that the use of the descriptive approach is the most suitable method for developing the scoring skills of the players.
Keywords: Physical abilities, Steady beats, sports field, Football.